Report on the dissemination Projects of HAQAA2 - Naidoo, Kethamonie; Assembe, Emile (HAQAA Initiative, 2023)
There were 14 projects funded that were aimed at disseminating the knowledge and skills of quality assurance (QA) in higher education gained during the HAQAA training program more widely in the countries of the participants. A brief overview of the diverse projects from Burkina Faso, Burundi, Cameroon, Comoros, Democratic Republic of the Congo, Egypt, Kenya, Madagascar, Mali, Mauritius, Mozambique, Niger, Uganda and Zambia are provided in this report. It is important upon conclusion of such a continental capacity development initiative to consider whether the project has achieved its aims. By having each project coordinator reflect on the completed project in a final report and an interview, it was possible to determine whether the objectives set for each project were achieved. The coordinators provided information on the outcomes achieved against the objectives set, the organisation of the intervention, and the challenges experienced and the manner in which the risks were managed, the sustainability considerations and their recommendations for future such projects. The main target group for the majority of the projects was the quality managers in the higher education institutions (HEIs), but many also included other stakeholders such as members of the regulatory bodies, executive management members of the HEIs and students. The most common focus was on the African Standards and Guidelines (ASGs) and other topics included were the African Quality Rating Mechanism (AQRM), the Pan African Quality Assurance Framework (PAQAF) and the Continental Education Strategy for Africa (CESA). Many projects included a focus on the tools and templates used for external and internal quality assurance. Countries are at different levels of maturity in terms of their regulatory frameworks, infrastructure and implementation of quality assurance. The COVID-19 pandemic created uncertainty during the planning phase of the project, and the six-month window period for the completion of the projects was reported to be too tight. The HAQAA Initiative has had a significant impact on building the capacity of QA professionals, and the dissemination has increased the reach of some institutions. However, it is evident that there is a need for more such training, as well as more in-depth training on specific aspects for those already trained.
Keywords: Quality Assurance; Higher Education